MAKNA GRAMATIKAL UMPASA BAHASA BATAK TOBA - Sitinjak, Zarmika Sitinjak; Sinaga, Mangatur Sinaga; ', Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research talked about the grammatical meaning of toba batak language umpasa. This research uses qualitative and descriptive approaches that purposes to describes the problem according to the reality. The object of this research is the grammatical meaning of umpasa Toba Batak language that found in the book of “Jambar Hata Dongan tu Ulaon Adat” and umpasa that found in the traditional wedding of Rodempo Hutabarat and Roi Sitinjak. This research uses written data that sources from book and visually which is from wedding’s video. The data obtained by uing observation technique from the video and book then transcribed to the written form and classified into ten umpasa with different grammatical meaning. Based on the data analysis found ten kinds of umpasa with the grammatical meaning. (1) umpasa pasu-pasu thet meaning benediction (2) umpasa that meaning hope to ancestry (3) umpasa that meaning expecations of longevity (4) umpasa that meaning advice on marriage (5) umpasa that meaning expectations about revenues (6) umpasa that meaning doctrine and prohibition (7) umpasa that meaning the importance of Batak culture (8) umpasa that meaning how to serving guest (9) umpasa that meaning demand for health (10) umpasa that meaning behave in family. Keywords: umpasa, grammatical meaning